"Stay at Home Reservation": Langkah Mitigasi dalam Pandemi Covid-19 - Faridiah Aghadiati Fajri; Muhammad Fakhrurrifqi; Dian Budi Santoso; Radhian Krisnaputra (IJNMT (International Journal of New Media Technology), 2021)
The Covid-19 pandemic condition that has hit the world has had a significant impact on various sectors. Health facilities need information system support in their services. Breaking the distribution chain can be done by maintaining a physical distance. However, in reality, people are still indifferent. There is a possibility that the patient is infected but shows no symptoms or is lying to the point of endangering medical personnel. In addition, there is a stigma in the community so that they are afraid to go to health facilities. Even though it cannot be denied that in certain conditions patients should still have their conditions checked by a doctor. The development of this online registration system aims to reduce the risk of contact between patients and medical personnel. The real-time queue monitoring feature helps patients to wait in line anywhere, so they are not in the patient's waiting room. This system is able to provide real-time queues for examinations in all polyclinics. This can reduce public anxiety about coming to health facilities. Index Terms— Covid-19; Health Facilities; Online Reservation; Pandemic; Realtime Queues